Розвиток творчих здібностей молодших школярів засобами ігор - Топорін, Олег Петрович (Харків : ХНУ імені В.Н. Каразіна, 2025)
Мета дослідження: теоретично обґрунтувати й розробити методику розвитку творчих здібностей молодших школярів засобами ігор.

The aim of the research is to theoretically substantiate and develop a methodology for the development of creative abilities in primary school children through games
Development of Creative Abilities in Primary School Children through Games
Keywords: SOCIAL SCIENCES::Social sciences::Pedgogical work; молодші школярі; творчі здібності; методика розвитку творчих здібностей; ігри; primary school children; creative abilities; methodology of developing creative abilities; games